Optical solitons in parabolic law medium: Jacobi elliptic function solution - Tchier, Fairouz; Aslan, Ebru Cavlak; İnç, Mustafa (Springer, 2016)
The aim of this paper is to obtain optical soliton solutions by nonlinear dispersion in parabolic law medium by using Jacobi elliptic functions. The presented problem is studied with Kerr law nonlinearity, and dark and bright solitons are acquired. Also, we develop the stability analysis for problem.
Keywords: Solitons; Jacobi elliptic functions; Optical soliton